Balgis Osman-Elasha, Erika Spanger-Siegfried, Nagmeldin Goutbi, Sumaya Zakicldin and Ahmed Hanafi - Elasha, Balgis Osman; Siegfried, Erika Spanger; Goutbi, Nagmeldin; Zakiicldin, Sumays; Hanafi, Ahmed (Annals of Arid Zone, 2016)
This paper is based on the outcome of a research work by the AIACC _AF 14 project in Sudan. The project is part of the "Global Assessment of Impacts and Adaptation to Climate Change (AIACC)" which is funded by the GEF through UNEP, executed by the International Academy of Science and implemented by Higher Council for Environment and Natural Resources (HCENR) in cooperation with Stockholm Environmental Institute-Boston (SEI_B). The main objective of the project was to enhance the scientific and technical information, to assess tne impact of climate change and to design cost-effective response measures which are needed to formulate national policy options. The motivation for the research work evolved out of a simple observation: that adaptation to a changing climate was clearly happening and that what was needed was a robust way of validating - and thus supporting - these successful experiences within the climate change community. Three case studies were conducted to assess the impacts of climate change on a range of socio-economic sectors and ecological systems at the national level and develop a range of adaptation options. The goal of the case studies was to illustrate and establish that certain sustainable livelihoods (and natural resource management) measures increase a community's resilience to today's climate-related shocks, and that it is possible to determine how such measures can be effectively implemented, supported and up-scaled, for lasting impact. To show this, each case study attempted to provide an assessment of SL/EM strategies adopted by the communities as well as assessing the local and national policies and conditions that support or inhibit successful measures. An impo'rtant assumption on which the research was based is that: sustainable livelihood assessment can fill the practical and conceptual gap that exists between local vulnerability to climate change and national/ intergovernmental policy processes .